Morphological Characteristics and Productivity of Guinea Grass (Panicum maximum CV Purple Guinea) Irradiated with Gamma-Ray - A. Fanindi; S. H. Sutjahjo; S. I. Aisyah; N. D. Purwantari (Faculty of Animal Science, Bogor Agricultural University, 2019)
Mutation breeding using gamma irradiation is one of the alternative ways to increase the variability and productivity of Guinea grass (Panicum maximum cv Purple guinea). The aimed of the study was to determine the dosage of gamma irradiation and morphological characters for high-yielding of the putative mutant of guinea grass. The Guinea grass seeds was irradiated by gamma- ray. The treatment was 8 doses of gamma irradiation and control (non-irradiated). The treatment was arranged in a randomized complete block design (RCBD) with 3 replications. The study was conducted for 3 generations, which were mutants 1 (M1), mutant 1 vegetative 1 (M1V1), and mutant 1 vegetative 2 (M1V2). The results showed that the gamma irradiation dose affected variables observed. The variables affected in M1 were fresh and dry weights of shoot, the number of tillers, and the length of the leaves. Whereas in the populations of M1V1 and M1V2, almost all characters were influenced by gamma irradiation, except stem diameter, length of internode, and leaf length. Gamma irradiation doses of 175 x 2 Gy, 250 Gy and 350 Gy in M1V1 and 100 x 2 Gy, 150x2 Gy and 175 x 2 Gy in M1V2 produced the high number of tillers, fresh and dry shoot weights. Heritability value and GCV of number of tillers, fresh and dry weight of shoot were high for M1V1 and M1V2 populations. These results indicated that gamma-ray irradiation can be applied to increase productivity and genetic variability of Guinea grass. The highest forage production was obtained at a dose of 100 x 2 Gy, which was 625 g/plant.